Genome‐wide association studies in biliary atresia. (11th May 2015) - Ningappa, Mylarappa; Min, Jun; Higgs, Brandon W.; Ashokkumar, Chethan; Ranganathan, Sarangarajan; Sindhi, Rakesh
<x xml:space="preserve">Abstract</x> Biliary atresia (BA) is a model complex disease resulting from interactions between multiple susceptibility loci and environmental factors. This perception is based on a heterogeneous phenotype extending beyond an absent extrahepatic bile duct to include gut and cardiovascular anomalies, and the association of BA with viral infections. Refractory jaundice and progression to cirrhosis shortly after birth can be fatal without surgical correction, and further suggests a pathogenesis during liver and bile duct development. Conclusive proof for a developmental origin would require documentation of disease progression in the perinatal or fetal liver, an impossible task for obvious reasons. We review three different sets of genome‐wide association studies (GWAS) from three different cohorts of BA patients by three different groups of investigators, which address this knowledge gap. Knockdown of each susceptibility gene identified by GWAS in zebrafish embryos impairs excretion of bile from the liver, duplicating the characteristic diagnostic finding seen in affected children. This finding is associated with impaired intrahepatic biliary network formation in zebrafish morphants. Although distinct, these susceptibility genes share several functions including roles in mechanisms for organogenesis (glypican 1 or GPC1, and adenosine diphosphate ribosylation factor 6, or ARF6) or a greater expression in fetal liver than in adult liver (adducin 3 or ADD3). Together, these studies emphasize the importance of the human evidence, and present opportunities to map novel pathways which explain the phenotypic heterogeneity of BA. WIREs Syst Biol Med 2015, 7:267–273. doi: 10.1002/wsbm.1303 For further resources related to this article, please visit the WIREs website.